Identification of new bacteria harboring qnrS and aac(6′)-Ib/cr and mutations possibly involved in fluoroquinolone resistance in raw sewage and activated sludge samples from a full-scale WWTP. (1st March 2017) - Paiva, Magna C.; Reis, Mariana P.; Costa, Patrícia S.; Dias, Marcela F.; Bleicher, Lucas; Scholte, Larissa L.S.; Nardi, Regina M.D.; Nascimento, Andréa M.A.
Abstract: Wastewater treatment plants (WWTPs) harbor bacteria and antimicrobial resistance genes, favoring gene exchange events and resistance dissemination. Here, a culture-based and metagenomic survey of qnrA, qnrB, qnrS, and aac(6′)-Ib genes from raw sewage (RS) and activated sludge (AS) of a full-scale municipal WWTP was performed. A total of 96 bacterial isolates were recovered from nalidixic acid-enrichment cultures. Bacteria harboring the aac(6′)-Ib gene predominated in RS, whereas qnrS -positive isolates were specific to AS. Novel qnrS - and aac(6′)-Ib-cr positive species were identified: Morganella morganii, Providencia rettgeri, and Pseudomonas guangdongensis (qnrS ), and Alcaligenes faecalis and P. rettgeri ( aac(6′)-Ib-cr ). Analysis of qnrS and aac(6′)-Ib sequences from isolates and clone libraries suggested that the diversity of qnrS is wider than that of aac(6′)-Ib . A large number of amino acid mutations were observed in the QnrS and AAC(6 ′ )-Ib proteins at previously undetected positions, whose structural implications are not clear. An accumulation of mutations at the C72, Q73, L74, A75 and M76 positions of QnrS, and D181 of AAC(6 ′ )-Ib might be important for resistance. These findings add significant information on bacteria harboring qnrS and aac(6′)-Ib genes, and the presence of novel mutations that may eventually emerge in clinical isolates. Highlights: Bacteria harboring the aac(6′)-Ib gene predominated in raw sewage. qnrS -positive bacteria were specific to activated sludge. First report of the qnrS gene in Providencia rettgeri and Pseudomonas guangdongensis . aac(6′)-Ib-cr : first report in Alcaligenes faecalis and Providencia rettgeri . QnrS and AAC(6′)Ib exhibited many amino acids alterations previously undetected.